1951
DOI: 10.1104/pp.26.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Changes Accompanying Pollination in Orchid Flowers. Ii. Respiration, Catalase Activity, and Chemical Constituents

Abstract: In a previous paper of this series (19), data have been presented to show that pollination in orchid flowers brings about considerable changes in their water balance. The present paper deals with the change in respiratory activity, catalase activity, and chemical constituents as consequences of pollination and auxin treatment. The general methods used in sampling and treatment of flowers are essentially the same as that earlier described (19). A general conclusion, based on all experimental facts presented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1953
1953
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These results are in good agreement with the analytical records for flowers, the naturally set young fruit of Pyrus malus (27), and the observations of carbohydrate changes after pollination or chemical treatment of orchids (12). Following pollination a rapid starch synthesis has been observed in ovaries of orchids (32) and ovaries of Aralia, Erodium and Pelargonium (14,16).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results are in good agreement with the analytical records for flowers, the naturally set young fruit of Pyrus malus (27), and the observations of carbohydrate changes after pollination or chemical treatment of orchids (12). Following pollination a rapid starch synthesis has been observed in ovaries of orchids (32) and ovaries of Aralia, Erodium and Pelargonium (14,16).…”
Section: Discussionsupporting
confidence: 79%
“…Marked changes in carbohydrate content in ovaries after pollination were observed in orclhids by HSIANG (12), and SESHAGIRAH (32) noted an increased starchl synthesis in the ovaries, receptacles, and pedicels immediately after fertilization which also has been pointed out as a common occurrence by IMARRE (16,19). The excision of young seeds usually leads to a reduction in starch and sugar content in associated tissues (17,19) with a corresponding increase in amylase activity.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The pollination-induced increase of respiration corresponds to previous studies in orchid flowers (Hsiang, 1951). Goh et al (1982) reported that much of the increase in Vanda flowers is centered in the placenta and exhibits three peaks, one of which occurs immediately after pollination.…”
Section: Transmission Of Chemical Messengersmentioning
confidence: 87%
“…Hew (1980) showed that carbohydrate metabolism in the mature orchid flower proceeded via the EMP pathway. A respiratory quotient of 1 has been observed for the column and perianth of Coelogyne mooreana, Cymbidium lowianum (Hsiang, 1951) and labellum of Oncidium goldiana (Hew, 1980). Whether or not changes occur in the respiratory pathway of orchid flowers during development remains unclear.…”
Section: Introductionmentioning
confidence: 99%